2012
DOI: 10.1542/peds.2011-2196
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Passive Smoke Exposure and Incidence of Asthma and Wheeze: Systematic Review and Meta-analysis

Abstract: OBJECTIVES: Exposure to passive smoke is a common and avoidable risk factor for wheeze and asthma in children. Substantial growth in the prospective cohort study evidence base provides an opportunity to generate new and more detailed estimates of the magnitude of the effect. A systematic review and meta-analysis was conducted to provide estimates of the prospective effect of smoking by parents or household members on the risk of wheeze and asthma at different stages of childhood. METHODS:We systematically sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
405
3
25

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 632 publications
(466 citation statements)
references
References 81 publications
19
405
3
25
Order By: Relevance
“…In a recent meta-analysis, comparing antenatal and postnatal smoke exposure on the incidence of asthma and wheeze, children exposed to either antenatal or postnatal tobacco smoke exposure had a 30–80% increased risk of developing wheezing and a 21–85% increased risk of developing asthma [62]. However, the strongest risk for the development of wheezing was in children under 2 years with postnatal tobacco smoke exposure (OR 1.70, 95% CI 1.24–2.35) while the risk of developing asthma was associated with antenatal maternal smoking (OR 1.85, 95% CI 1.35–2.53) [62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, comparing antenatal and postnatal smoke exposure on the incidence of asthma and wheeze, children exposed to either antenatal or postnatal tobacco smoke exposure had a 30–80% increased risk of developing wheezing and a 21–85% increased risk of developing asthma [62]. However, the strongest risk for the development of wheezing was in children under 2 years with postnatal tobacco smoke exposure (OR 1.70, 95% CI 1.24–2.35) while the risk of developing asthma was associated with antenatal maternal smoking (OR 1.85, 95% CI 1.35–2.53) [62].…”
Section: Resultsmentioning
confidence: 99%
“…However, the strongest risk for the development of wheezing was in children under 2 years with postnatal tobacco smoke exposure (OR 1.70, 95% CI 1.24–2.35) while the risk of developing asthma was associated with antenatal maternal smoking (OR 1.85, 95% CI 1.35–2.53) [62]. By contrast, in a large population-based prospective cohort study, continued maternal smoking during pregnancy led to increased risk of early and persistent wheezing (OR 1.24, 95% CI 1.01–1.52; OR 1.48, 95% CI 1.13–1.95) and asthma (OR 1.65, 95% CI 1.07–2.55) [63].…”
Section: Resultsmentioning
confidence: 99%
“…19 Induce cambios en el crecimiento pulmonar, hiperreactividad de las vías respiratorias, deterioro de la adaptación inmune a los patógenos virales, disminución del desarrollo del sistema inmune pulmonar y cambios inmunológicos que favorecen el desarrollo de la enfermedad alérgica. 20 Además, la inducción de estrés oxidativo y las modificaciones en la colonización bacteriana de las mucosas provocan mayor penetración de alérgenos.…”
Section: Humo Del Tabacounclassified
“…A study that evaluated the effects of maternal smoking during pregnancy on asthma and wheezing in 5,762 school-aged children showed that in utero exposure to maternal smoking was associated with increased prevalence of physician-diagnosed asthma [odds ratio (OR) = 1.8], asthma with current symptoms (OR=2.3), asthma requiring medication use in the previous 12 months (OR= 2.1), lifetime history of wheezing (OR=1.8), and emergency room visits during the previous year (OR=3.4) (11). Also, the exposure to prenatal maternal smoking was associated with increase in risk of wheeze (40%) and asthma (20%) in children aged ≤2 years in a systematic review that included 79 prospective studies (OR=1.41 and OR=1.85) (12). Silvestri et al (13) reported that exposure to maternal prenatal smoking was associated with an increased risk of wheezing in <6-year-olds (OR=1.36) and wheezing or asthma in ≥6-year-olds (OR=1.22) in a systematic review.…”
Section: Smoking During Pregnancymentioning
confidence: 99%